TECHNOLOGY AND EMPIRE: Comparing Dutch and British Maritime Technologies During the Napoleonic Era (1792–1815) - Mollema, Ivor (East Carolina University, 2015)
The two ships, Bato (1806) and Brunswick (1805) wrecked in Simons Bay, South Africa, provide an opportunity to compare British and Dutch maritime technologies during the Napoleonic Era (1792–1815). The former was a Dutch 74-gun ship of the line and the latter a British East Indiaman. Their remains reveal pertinent information about the maritime technologies available to each European power. Industrial capacity and advanced metal working played a significant role in ship construction initiatives of that period, while the dwindling timber supplies forced invention of new technologies. Imperial efforts during the Napoleonic Era relied on naval power. Maritime technologies dictated imperial strategy as ships were deployed to expand or maintain colonial empires. Naval theorists place the strategy into a wider spectrum and the analysis of the material culture complements further understanding of sea power. The study also recommends management options to preserve the archaeological sites for future study and to showcase for heritage tourism.
Keywords: Dutch; Napoleonic; Marine engineering--Europe; Historic ships--Netherlands; Historic ships--Great Britain; Shipwrecks--South Africa